Mapping the Critical Intellectual Capital of IRD (Brazilian Journal of Radiation Sciences, 2019)
Currently, several studies that dealing with the subject of knowledge management aiming the preservation and transfer of intellectual capital, leading to the retention of knowledge retention in an institution or organization.   The National Nuclear Energy Commission (CNEN) of Brazil, the federal authority responsible for the national nuclear energy standards, research, development, and regulation, has been facing difficulties in human resources due to the increase in the number of retirements and the  lack of replacement of people, especially with the scientific-technical profile, as a result of the cancelation of public employee hiring in the country.The purpose of this study is to map the critical technical areas at the Institute of Radiation Protection and Dosimetry (IRD), from CNEN. A model used by the International Atomic Energy Agency (IAEA) was adopted here, which takes into account the time for retirement, beyond the specificity and availability of knowledge.As a result of the study, it was possible to identify that in all end-areas, the IRD has employees that retain the critical knowledge, but they are hard to be replaced or transfer their knowledge. Therefore, a management plan should be implemented for the retention and transfer of knowledge specific to the nuclear area, which is essential for IRD to continue to meet its strategic objectives and that also contributes to minimize the impacts to the country generated by the loss of this sensitive and specialized knowledge.